JAG/BSG national survey of UK endoscopy services: impact of the COVID-19 pandemic and early restoration of endoscopy services. Issue 4 (21st August 2020) - Catlow, Jamie; Beaton, David; Beintaris, Iosif; Shaw, Tim; Broughton, Raphael; Healey, Chris; Penman, Ian; Coleman, Mark; Rutter, Matt
Abstract : Introduction: The COVID-19 pandemic has profoundly affected UK endoscopy workload. The Joint Advisory Group on GI endoscopy and British Society of Gastroenterology issued guidelines on endoscopy service delivery changes and restoration. We surveyed UK endoscopy clinical leads to gain insights into service restoration. Methods: A Google Forms-designed survey, assessing endoscopy provision, Covid minimisation and referral pathways was circulated to all UK endoscopy leads. The survey was open between 19 and 24 May 2020. Results: 97 endoscopy leads completed the survey, with all UK nations and regions represented. Analysis showed 20% of endoscopy services were not providing endoscopy. Workload limitations were due to enforced interprocedural downtime (92%; with some services enforcing >1-hour downtime between procedures), social distancing (88%) and working in personal protective equipment (PPE) (87%). 91% of services reported a referral backlog (urgent median 2 months, routine median 6 months). 96% of services reported no current problems accessing PPE. Level 1/2 PPE use in colonoscopy was not uniform. 63% of services routinely swab patients for COVID-19 before endoscopy, 88% of services do not routinely swab asymptomatic staff. Comments addressed reducing endoscopy demand through vetting and changing referral criteria, the mostly commonly cited strategy being increased faecal immunochemical testing in symptomatic patients (70% of services). Conclusion: This survey demonstrates the pandemic's profound impact on UK endoscopy. Challenges include standardising Covid-minimisation strategies and recovering staffing levels. To improve endoscopy services, there is a need to refine referral pathways, improve vetting and clarify guidance on downtime and PPE within endoscopy.